"Homemade": The Vicious Circle of Household Pharmaceutical Waste. (1st September 2020) - MITKIDIS, Katerina; MITKIDIS, Panagiotis
Abstract : Pharmaceutical science has provided humans with better and cheaper treatments. However, with improved access to medicines, the amount of pharmaceutical waste also grows. Pharmaceutical waste is regularly mismanaged by households, which is considerably and unnecessarily adding to the "pharmaceuticals in the environment" problem. Redesigning existing pharmaceutical takeback schemes and their regulation is a potential step towards a reduction of the problem. Interdisciplinary research between the fields of psychology, law, public health and medical science is necessary to tackle the issue and to design effective regulation steering responsible patient behaviours.